2010
DOI: 10.5713/ajas.2011.10195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Formic Acid Administration in the Drinking Water on Performance, Intestinal Microflora and Carcass Contamination in Male Broilers under High Ambient Temperature

Abstract: In this study, we examined the effects of formic acid administration to the drinking water on performance, intestinal microflora and carcass contamination in male broilers. A total of 312 day-old male broiler chicks were allocated to two groups with three replicates. The first group (control) received normal drinking water (pH 7.4) during the experiment. The second group consumed acidified drinking water (pH 4.5) after 5 d of age. At 43 d of age, twelve birds were randomly selected from the control group to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 32 publications
1
16
0
4
Order By: Relevance
“…(2010) found that dietary supplementation of organic acid mixtures (fumaric acid, calcium format, calcium propionate, potassium sorbate, calcium butyrate, calcium lactate and hydrogenated vegetable oil) is more efficient than the antibiotic growth promoter (Enramycin) in decreasing intestinal E. coli and Salmonella spp. Different studies by ( Byrd et al., 2001 , Açkgöz et al., 2011 , Hamed and Hassan, 2013 ) indicated that addition of organic acid to the drinking water helps to reduce the level of pathogens in the water and the crop/proventriculus, to regulate gut micro flora. It is believed that the organic acid administration in feed or water mainly metabolized and absorbed in the upper gastro-intestinal segments of poultry as recorded by ( Thompson and Hinton, 1997 , Van Immerseel et al., 2006 , Hassan et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2010) found that dietary supplementation of organic acid mixtures (fumaric acid, calcium format, calcium propionate, potassium sorbate, calcium butyrate, calcium lactate and hydrogenated vegetable oil) is more efficient than the antibiotic growth promoter (Enramycin) in decreasing intestinal E. coli and Salmonella spp. Different studies by ( Byrd et al., 2001 , Açkgöz et al., 2011 , Hamed and Hassan, 2013 ) indicated that addition of organic acid to the drinking water helps to reduce the level of pathogens in the water and the crop/proventriculus, to regulate gut micro flora. It is believed that the organic acid administration in feed or water mainly metabolized and absorbed in the upper gastro-intestinal segments of poultry as recorded by ( Thompson and Hinton, 1997 , Van Immerseel et al., 2006 , Hassan et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The control group (C-gr) received basal diet and tap water. Citric acid group (CAgr) received basal diet and acidified drinking water (pH 4.5) (Açıkgözet et al, 2011) with CA monohydrate (Sigma, Australia). Acetic acid group (AA-gr) received basal diet and acidified drinking water of pH= 4.5 (Açıkgözet et al, 2011) with AA (El Gomhoria Co., Egypt).…”
Section: Experimental Designmentioning
confidence: 99%
“…The presence of lactic acid bacteria in the crop is considered a barrier to Salmonella spp., so disrupting this resident crop microbiota could be problematic for achieving a successful reduction in Salmonella GIT colonization (144). Less impact may occur in the lower part of the avian GIT as Açikgöz et al (145) did not detect differences in total intestinal bacteria or E. coli in 42-day-old broilers receiving formic acid acidified water. As the authors speculated, this might be due to the formic acid being metabolized in the upper part of the GIT as noted by others for externally introduced SCFA (128, 129).…”
Section: Interaction Of the Non-pathogen Gastrointestinal Microbiota mentioning
confidence: 99%